Multi-input single-output control for extending the operating range: Generalized split range control using the baton strategy. (July 2020) - Reyes-Lúa, Adriana; Skogestad, Sigurd
Abstract: Split range control is used to extend the steady-state operating range for a single output (controlled variable) by using multiple inputs (manipulated variables). The standard implementation of split range control uses a single controller with a split range block, but this approach has limitations when it comes to tuning. In this paper, we introduce a generalized split range control structure that overcomes these limitations by using multiple independent controllers with the same setpoint. Undesired switching between the controllers is avoided by using a baton strategy where only one controller is active at a time. As an alternative solution we consider model predictive control (MPC), but it requires a detailed dynamic model and does not allow for using only one input at a time. Highlights: Generalized control structure for two or more inputs and one output. Control structure to extend the steady-state operating range of an output. A simple baton strategy avoids undesired switching of the active input. PID-based control structure that allows to individually tune the controller for each input.